Structural basis of ubiquitin ligase Nedd4-2 autoinhibition and regulation by calcium and 14-3-3 proteins - Janosev, Masa; Kosek, Dalibor; Tekel, Andrej; Joshi, Rohit; Honzejkova, Karolina; Pohl, Pavel; Obsil, Tomas; Obsilova, Veronika (Nature communications, 2025)
Nedd4-2 E3 ligase regulates Na+ homeostasis by ubiquitinating various channels and membrane transporters, including the epithelial sodium channel ENaC. In turn, Nedd4-2 dysregulation leads to various conditions, including electrolytic imbalance, respiratory distress, hypertension, and kidney diseases. However, Nedd4-2 regulation remains mostly unclear. The present study aims at elucidating Nedd4-2 regulation by structurally characterizing Nedd4-2 and its complexes using several biophysical techniques. Our cryo-EM reconstruction shows that the C2 domain blocks the E2-binding surface of the HECT domain. This blockage, ubiquitin-binding exosite masking by the WW1 domain, catalytic C922 blockage and HECT domain stabilization provide the structural basis for Nedd4-2 autoinhibition. Furthermore, Ca2+-dependent C2 membrane binding disrupts C2/HECT interactions, but not Ca2+ alone, whereas 14-3-3 protein binds to a flexible region of Nedd4-2 containing the WW2 and WW3 domains, thereby inhibiting its catalytic activity and membrane binding. Overall, our data provide key mechanistic insights into Nedd4-2 regulation toward fostering the development of strategies targeting Nedd4-2 function.
Keywords: Models, Molecular; elektronová kryomikroskopie; Calcium; Nedd4 Ubiquitin Protein Ligases; HEK293 buňky; Protein Binding; proteinové domény; HEK293 Cells; Humans; ubikvitinace; vápník; molekulární modely; Ubiquitination; 14-3-3 Proteins; vazba proteinů; ubikvitinligasy Nedd4; lidé; Cryoelectron Microscopy; Protein Domains; proteiny 14-3-3